2007
DOI: 10.1002/smi.1134
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the physical environment on job performance: towards a theoretical model of workspace stress

Abstract: Studies of stress in the work environment pay little attention to features of the physical environment in which work is performed. Yet evidence is accumulating that the physical environment of work affects both job performance and job satisfaction. Contemporary research on stress in the work environment typically focuses on psychosocial factors that affect job performance, strain and employee health, and does not address the growing body of work on the environmental psychology of workspace. This paper reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
274
2
25

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(342 citation statements)
references
References 30 publications
10
274
2
25
Order By: Relevance
“…According to Vischer (2007), the biggest factor contributing to worker satisfaction and performance is the floor configuration and layout. In settings where employees are closer to each other, with few to no barriers among them as in the case of open-plan offices, opportunities for communication are higher and it is well-known that a good communication flow is the gatekeeper to cooperation, knowledge sharing and cohesion in groups (Chigot, 2003).…”
Section: Features Of the Physical Work Environment And Their Effects mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Vischer (2007), the biggest factor contributing to worker satisfaction and performance is the floor configuration and layout. In settings where employees are closer to each other, with few to no barriers among them as in the case of open-plan offices, opportunities for communication are higher and it is well-known that a good communication flow is the gatekeeper to cooperation, knowledge sharing and cohesion in groups (Chigot, 2003).…”
Section: Features Of the Physical Work Environment And Their Effects mentioning
confidence: 99%
“…Under these circumstances the visual and acoustic privacy is hindered, which in turn may negatively affect one's emotions and behaviors toward others (e.g., leading people to be less tolerant, more keen on conflict) as well as performance. One of the primary complaints of workers in open-plan offices is indeed the discomfort caused by high levels of noise (Vischer, 2007). While other causes of employee dissatisfaction with open-plan offices include increased frequency of uncontrolled interactions, cognitive overload and stress leading to lower levels of concentration and motivation as well as lack of psychological privacy, noise is described as the factor employees would most like to control (Davis et al, 2011).…”
Section: Features Of the Physical Work Environment And Their Effects mentioning
confidence: 99%
“…Previous studies from different perspectives have shown that the perceived quality of the physical work environment have influenced in employees' job perception, satisfaction, psychological stress, attitudes and overall performance (Sundstrom et al, 1994;George and Brief, 1992;McGuire and McLaren, 2009;Thatcher and Milner, 2012;Vischer, 2007;Huang et al, 2004;Hwang and Kim, 2013;O'Neill, 2010;Carlopio, 1996;Al-Anzi, 2009;Hua et al, 2011;Davis et al, 2011). Briner (2000) suggested that the nature and arrangement of designing and furnishing a place influence the frequency and type of interaction that takes place in an environment.…”
Section: The Role Of Work Environment Design On Individual Attitude Amentioning
confidence: 99%
“…For instance, Amabile (1996) explained that physical workspaces which were designed to be motivating can promote the level of creativity; however this effect is not stronger than other aspects of the work environment such as social environment. Previous studies from different perspectives have shown that the perceived quality of the physical work environment influence people creativity (see for example: McCoy and Evans, 2002;Vithayathawornwong et al, 2003;Vischer, 2007;Oksanen and Ståhle, 2013). In fact, previous studies indicated the direct or indirect role of certain features of the physical work environment on creativity via mood (Hedge, 1982;Larsen et al, 1998;Shibata and Suzuki, 2004).…”
Section: The Role Of Physical Work Environment On Individual and Orgamentioning
confidence: 99%
See 1 more Smart Citation